Analytical Method Development And Validation Of RP-HPLC Method For Estimation Of Lumateperone In Bulk And Pharmaceutical Dosage Form - Undre, Darshana; Shilimkar, Vaibhav (Journal of Neonatal Surgery, 2025)
Objective: To develop and validate precise, accurate, and robust analytical methods—UV-Visible Spectrophotometry and Reversed Phase High-Performance Liquid Chromatography (RP-HPLC)—for the estimation of Lumateperone Tosylate in bulk and pharmaceutical dosage forms. Methods: The UV spectrophotometric method involved selecting 227 nm as the analytical wavelength using a 50:50 v/v water:methanol diluent. Linearity was established between 5–15 µg/mL (R² = 0.9997). The RP-HPLC method was developed using a Phenomenex C18 column with a mobile phase of phosphate buffer (pH 6.0):methanol (55:45 v/v), a flow rate of 1.2 mL/min, and detection at 227 nm. Validation parameters such as accuracy, precision, linearity, system suitability, and robustness were assessed following ICH Q2(R1) guidelines¹. Results: The UV method demonstrated good linearity (R² = 0.9997), recovery (98.0%–102.0%), and precision (RSD < 2%). The optimized HPLC method (retention time 4.1 min) showed acceptable asymmetry (1.21) and theoretical plates (>7500), with consistent assay results and % RSD within limits. The methods were successfully applied for quantitative estimation of Lumateperone in capsules². Conclusion: Both methods were simple, reliable, and suitable for routine quality control of Lumateperone. These findings provide an analytical foundation for future pediatric formulation development of Lumateperone, pending neonatal pharmacokinetic research³.